Regional aspect of the digital economy development: opportunities and prospects on the example of the Republic of Adygea - S. N. Obmachevskaya (Новые технологии)
The article discusses current issues of the development of the digital economy in the regions based on their fundamental capabilities. The characteristic features of the development of information technologies in the socio-economic sphere of the region have been analyzed. The digitization of the economy causes a two-sided reaction in society: on one hand, it denies the need for it, identifies threats and risks, on the other, promotes global trends and possible positive effects. Studies have shown that at the present stage more than 80% of the population use digital technologies, which can be considered as the initial stage of the development of the digital economy. The article substantiates the idea of priority development of digital technologies in the field of socio-economic activities. The study of regional aspects of digitalization allows the author to come to the conclusion about the need for a synergistic approach to the implementation of the Digital Economy Program in the health sector. The characteristic features of creating digital platforms have been highlighted and described. The author traces the trends and results of the implementation of certain aspects of information and communication technologies in the context of public medical institutions in the region. The stages of formation and development of medical information systems and technologies in the Republic of Adygea have been identified In chronological order. Prospects for the creation of a regional medical digital platform as a key factor in raising the level of the socio-economic development of the region and the effective interaction of the subjects of the medical services market have been analyzed. The main advantage of the proposed model is the synergistic, dialogic and communicative aspect. The positive effect in the development of socio-economic processes in the region allows us to draw conclusions about the prospects for the development of this area of the digital economy.